Nanofat Injection for the Treatment of Abnormal Scar Compared with Triamcinolone Acetonide - Almas Mirza Murastomo; Agus Santoso Budi; Magda Rosalina Hutagalung; Vijayendran Swaminathan; Hanifiya Samha Wardhani (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Hypertrophic and keloid scars arise from abnormal healing processes in fibrous tissue where tissue repair and regeneration control mechanisms do not work well. The standard treatment is an intralesional steroid injection with triamcinolone acetonide (TA). This method is effective, but there are some side effects include hypopigmentation and tissue atrophy. The nanofat method has been applied to various skin conditions with fewer side effects. Therefore, the use of nanofat with its regenerative properties can be expected to yield better results. This study aims to compare the decrease in modified Vancouver Scar Scale (VSS) score after nanofat administration and TA in abnormal scars. Methods: This is an experimental study with a pre- and posttest control group design. Twenty participants with abnormal scars from the Outpatient clinic of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, were recruited. Nanofat and TA were applied once. The evaluation of modified VSS was conducted twice (pre- and posttest 8 weeks after therapy). Results: There was a significant decrease in the modified VSS pretest score compared to posttest after nanofat therapy (P = 0.004). There was a significant decrease in the modified VSS pretest score compared to posttest after (P TA therapy = 0.004). There was no significant difference in VSS score between treatment with nanofat compared to TA in patients with abnormal scars. Conclusion: There was a significant decrease in the modified VSS score after nanofat and TA therapy. Nanofat has the same effectiveness as TA for abnormal scar therapy.